(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2012)
This paper considers evidence of the urgency of new disciplinary interactions from understanding other ways of knowing, involved in modern artificial intelligence, which is the science of epistemology from ancient study of human knowledge, and how individuals act to develop structures of thought. With the advent of Artificial Intelligence, at the Dartmouth’s conference, epistemology faces a new challenge, consider the "knowledge" of machines and structures that allow artificial thinking, what could be the birth of a new subfield of epistemology from the perspective of complexity to be called android epistemology. The design of literature is a documentary analysis, based on the critical tool and the author’s experience that allows us to reflect on the impact of epistemology from the perspective of complexity and artificial intelligence.